Facing a Disruptive Face: Embodiment in the Everyday Experiences of “Disfigured” Individuals - Yaron, Gili; Meershoek, Agnes; Widdershoven, Guy; van den Brekel, Michiel; Slatman, Jenny (Human Studies, 2017)
In recent years, facial difference is increasingly on the public and academic agenda. This is evidenced by the growing public presence of individuals with an atypical face, and the simultaneous emergence of research investigating the issues associated with facial variance. The scholarship on facial difference approaches this topic either through a medical and rehabilitation perspective, or a psycho-social one. However, having a different face also encompasses an embodied dimension. In this paper, we explore this embodied dimension by interpreting the stories of individuals with facial limb absence against the background of phenomenological theories of the body, illness and disability. Our findings suggest that the atypical face disrupts these individuals’ engagement with everyday projects when it gives rise to disruptive perceptions, sensations, and observations. The face then ceases to be the absent background to perception, and becomes foregrounded in awareness. The disruptions evoked by facial difference call for adjustments: as they come to terms with their altered face, the participants in our study gradually develop various new bodily habits that re-establish their face’s absence, or relate to its disruptive presence. It is through these emergent habits that facial difference comes to be embodied. By analyzing the everyday experiences of individuals with facial limb absence, this article provides a much-needed exploration of the embodied aspects of facial difference. It also exemplifies how a phenomenological account of illness and disability can do justice both to the impairments and appearance issues associated with atypical embodiment.